2018
DOI: 10.4172/2167-0277.1000282
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea as a Risk Factor for Atrial Fibrillation: A Meta-Analysis

Abstract: Objectives To conducted a meta-analysis assessing the relationship between Obstructive Sleep Apnea (OSA) and the risk of Atrial Fibrillation (AF) Methods We searched PUBMED, Medline, and Cochrane Library using the keywords “atrial fibrillation”, “obstructive sleep apnea” and “sleep disordered breathing (SDB)”. All subjects included had established diagnosis of OSA/SDB. We then compared the occurrence of AF versus no AF. Analysis done with Comprehensive Meta-Analysis package V3 (Biostat, USA). Results A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 22 publications
1
41
1
8
Order By: Relevance
“…Obstructive sleep apnea (OSA) is strongly associated with an increased risk of atrial fibrillation (AF). [1][2][3][4][5] The prevalence of OSA in populationbased studies ranges from 3% to 49% while the prevalence is AF c 2018 Chinese Cochrane Center, West China Hospital of Sichuan University and John Wiley & Sons Australia, Ltd population is up to 21% to 74%. 3,6,7 Several potential mechanisms for OSA-induced AF have been proposed including intermittent hypoxemia and hypercapnia, sympathetically mediated vasoconstriction and surge in blood pressure during an apneic episode leading to left atrial (LA) enlargement, and atrial remodeling and fibrosis due to oxidative stress and inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is strongly associated with an increased risk of atrial fibrillation (AF). [1][2][3][4][5] The prevalence of OSA in populationbased studies ranges from 3% to 49% while the prevalence is AF c 2018 Chinese Cochrane Center, West China Hospital of Sichuan University and John Wiley & Sons Australia, Ltd population is up to 21% to 74%. 3,6,7 Several potential mechanisms for OSA-induced AF have been proposed including intermittent hypoxemia and hypercapnia, sympathetically mediated vasoconstriction and surge in blood pressure during an apneic episode leading to left atrial (LA) enlargement, and atrial remodeling and fibrosis due to oxidative stress and inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a dog model of tachypacing-induced AF, strong vagal nerve stimulation that slows the sinus rate by at least 60% facilitates AF inducibility, but moderate vagal nerve stimulation that slows the sinus rate by only 10–30% does not shorten atrial ERP or affect AF inducibility ( Takei et al, 2001 ; Zhang et al, 2009a ). Low-level stimulation of the extrinsic cardiac autonomic nervous system can suppress AF by inhibiting the autonomic outflow of intrinsic cardiac autonomic nervous system ( Zhang et al, 2009c ; Shen et al, 2011 ; Yu et al, 2011 ). In fact, low-level vagus nerve stimulation (LLVS) can suppress tachypacing-induced adrenergic AF as well was cholinergic-induced AF by mitigating neural remodeling by the intrinsic cardiac autonomic nervous system, thereby preventing and reversing adverse atrial electrical and structural remodeling ( Sheng et al, 2011 ; Kusunose et al, 2014 ; Beaumont et al, 2015 ).…”
Section: Redefining Therapeutic Goalsmentioning
confidence: 99%
“…In the United States, extended longevity from medical advances has led to the projection of up to 15 million patients diagnosed with AF by 2050 (Miyasaka et al, 2006;Colilla et al, 2013). Modifiable risk factors for developing AF within 10 years (Schnabel et al, 2009) include hypertension, diabetes mellitus (Patel et al, 2014), coronary artery disease (Peigh et al, 2020), heart failure, obesity (Thacker et al, 2013), and obstructive sleep apnea (Youssef et al, 2018). Non-modifiable AF risk factors include valvular heart disease (Banerjee et al, 2019), hypertrophic cardiomyopathy (Olivotto et al, 2001), and congenital heart disease (Hu and Lin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Patel et al evaluated 3000 patients undergoing catheter ablation of AF and found an 11% significant reduction in recurrence in patients on CPAP versus control [ 32 ]. Furthermore, in a randomized control trial of 18 patients with OSA who had greater than 10 ventricular premature beats during sleep, Ryan et al reported a 58% significant reduction in premature beats during sleep in patients treated with CPAP [ 33 37 ].…”
Section: Osa and Cardiac Arrhythmiasmentioning
confidence: 99%